1993
DOI: 10.1017/s0950268800056648
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition and invasiveness of different serotypes of Streptococcus pneumoniae in young children

Abstract: SUMMARYRates of acquisition and mean duration of nasal carriage of different serotypes of Streptococcus pneumoniae have been estimated by fitting a stochastic model to longitudinal carriage data in children from Papua New Guinea. Immunogenicity and two indices of relative invasiveness were determined for each serotype. Immunogenic serotypes were less frequently acquired and were carried for shorter periods, but no relationship between immunogenicity and invasiveness was apparent using either index of invasiven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
86
0
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(96 citation statements)
references
References 19 publications
(54 reference statements)
9
86
0
1
Order By: Relevance
“…Indeed, in this study approximately half of the children <3 years of age carried the organism for over half of the total study period, which is in agreement with a previous study conducted in Oxford [8]. This presumably reflects both longer duration of carriage in children, as has been previously reported [4,10] together with more frequent acquisition compared to adults. Our results also suggest children are frequently the route of entry of the bacterium into the household, with a preponderance of those identified to be carrying for the first time being young children.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Indeed, in this study approximately half of the children <3 years of age carried the organism for over half of the total study period, which is in agreement with a previous study conducted in Oxford [8]. This presumably reflects both longer duration of carriage in children, as has been previously reported [4,10] together with more frequent acquisition compared to adults. Our results also suggest children are frequently the route of entry of the bacterium into the household, with a preponderance of those identified to be carrying for the first time being young children.…”
Section: Discussionsupporting
confidence: 92%
“…serotype 1 are not covered by the 7-valent vaccine. These serotypespecific variations in ' invasiveness ' have been noted by other groups both in the United Kingdom [26] and elsewhere [10]. However, this comparison should be undertaken with caution as it is well documented that serotype-specific duration of carriage varies -thus, serotype 1 for example, may be carried more widely, but for a very short period of time.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Acquisition and clearance rates are thus estimated for carriage of any Pnc serotype. Serotype-specific differences in Pnc acquisition and clearance rates were shown in the past [12] and represent a very critical issue in terms of future disease burden and impact of vaccination policies. Here some baseline information on Pnc transmission dynamics are derived and, although the model allows successive positive tests to be attributed to recovery and reacquisition, it does not exploit the information provided by a change of the serotype carried.…”
Section: Discussionmentioning
confidence: 99%
“…In this type of study, individuals are swabbed at regular intervals, their carriage status is assessed and inference on their rate of acquisition and on the duration of carriage can be obtained. Smith et al [12] using longitudinal carriage data collected in Papua New Guinea found that Pnc serotypes vary widely in their acquisition rates and in the length of time for which they persist. An inverse relationship between duration of carriage and age was shown by Ekdahl et al [13] who studied Pnc carriage using data from an intervention project in Sweden.…”
Section: Previous Workmentioning
confidence: 99%